Establecimiento de una guía de educación ambiental para la adecuada gestión de residuos sólidos en el sitio “La Venturita”, cantón Bolívar - Quintero Zamora, Shirley Carolina (2023)
This research was developed at "La Venturita" site, Bolívar canton, Manabí province; with the aim of establishing an environmental education guide for the proper management of solid waste. For this purpose, it began with the determination of solid waste management at "La Venturita" site, which was carried out through observation in the study area, together with an interview with the president of the site, Lusbelia García and a survey of 163 randomly selected people. Subsequently, an environmental education guide was designed for the inhabitants of the site, in order to provide guidelines for them to apply proper management of the waste generated from their homes. Finally, the guide was socialized in the presence of authorities and other residents. The results show that 99% of the inhabitants in "La Venturita" are unaware of the measures for proper waste management; therefore, they are not trained to use the basic principles of proper waste management in their community. Regarding the evaluation applied after socialization, 100% of the residents stated that they were willing to put into practice the procedures for the correct management of their waste; in addition, they expressed their interest in the structure and contents of the guide, due to its importance for the community. In conclusion, an environmental education guide allows society to instruct itself in sustainable and healthy practices for the environment.